What's the factorial moment of negative binomial distribution, if $$ \Pr(X = k) = \binom{k+r-1}{k} p^k(1-p)^r$$

I tried it: $$ E\left[ \frac{X!}{(X-m)!}\right] = \sum_{k=m}^{\infty} \frac{(r+k-1)!}{(k-m)!} \cdot p^k = \sum_{k=0}^{\infty} \frac{(m+r-1+k)!}{k!} \cdot p^{k+m} = \sum_{k=0}^{\infty} (m+r-1)! \cdot \frac{(m+r-1+k)!}{k! \cdot (m+r-1)!} \cdot p^k \cdot p^m = p^m \cdot (m+r-1)! \cdot \sum_{k=0}^{\infty} \binom{m+r-1+k}{k} \cdot p^k. $$

What's next?

  • 1
    $\begingroup$ Please include your thoughts and efforts in this and future posts. Formatting tips here. $\endgroup$
    – Em.
    Jan 11, 2016 at 8:02
  • 1
    $\begingroup$ PGF of $NB(r;p)$ is $f(z)=(\frac{1-p}{1-pz})^r$ and $E(X)_k=f^{(k)}(1)$. $\endgroup$
    – A.S.
    Jan 11, 2016 at 8:04
  • $\begingroup$ I tried do this: $$ \sum_{k=m}^{\infty} \frac{(r+k-1)!}{(k-m)!} \cdot p^k = \sum_{k=0}^{\infty} \frac{(m+r-1+k)!}{k!} \cdot p^{k+m} = \sum_{k=0}^{\infty} (m+r-1)! \cdot \frac{(m+r-1+k)!}{k! \cdot (m+r-1)!} \cdot p^k \cdot p^m = p^m \cdot (m+r-1)! \cdot \sum_{k=0}^{\infty} \binom{m+r-1+k}{k} \cdot p^k. $$ $\endgroup$
    – user304251
    Jan 11, 2016 at 8:10
  • $\begingroup$ user304251, you should put your attempt in the question itself rather than in the comment. $\endgroup$
    – hermes
    Jan 11, 2016 at 8:48

2 Answers 2


Just to give an actual answer for posterity, let us use the hint by @A.S. The probability generating function (PGF) is: $$ f(z) = \left(\frac{1-p}{1-pz}\right)^r, $$ and thus $$ f^{(k)}(z) = \frac{p^k \left(\frac{1-p}{1-pz}\right)^r \prod_{i=0}^{m-1} r + i}{(1-pz)^k}, $$ so finally $$ E[(X)_m] = \frac{p^m \prod_{i=0}^{m-1} r + i}{(1-p)^m}. $$


While you can get the $k$th factorial moment from the generating function, you can also calculate the value directly-here's how.

First rewrite: $$\mathbb{E}[(X)_k] = \sum_{x\geq 0} {x+r-1 \choose x} (x)_k q^xp^r,$$ by taking out $q^k$ and $p^r$ to get $$p^rq^k\sum_{x\geq 0} {x+r-1 \choose x} (x)_k q^{x-k}.$$ Note here for brevity, I write $q=1-p$.

Next use $D^kx^a=(a)_kx^{a-k}$ where $D$ is the derivative operator.

$$p^rq^k\sum_{x\geq 0} {x+r-1 \choose x} (x)_k q^{x-k} = p^rq^k\sum_{x\geq 0} {x+r-1 \choose x} (-D)^kq^{x}.$$

Now take interchange the sum and derivative operator-you can show that this is a valid operation in this context via Fubini's theorem. Now consider,

$$p^rq^k(-D)^k \underbrace{\sum_{x\geq 0} {x+r-1 \choose x} q^{x}}_{=p^{-r}}=p^rq^k(-D)^kp^{-r}.$$

Now you can also show that $(-D)^kp^{-r} = r^{(k)}p^{-(r+k)}$, where the $r^{(k)}$ denotes a rising factorial. Using this fact gives us


which simplifies to


For $r=1$ this gives the formula for the $k$th factorial moment of a geometric random variable, $k!\left(\frac{q}{p}\right)^k.$

This is a-slightly-different approach than the generating function but gives you the same formula. Notice that I wrote the negative binomial as failures before the $r$th success and the OP and the other answer written give the formula where the definition is number of successes before the $r$th failure so to compare you need to change my $p$s and $q$ to match.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.